PENENTUAN KECEPATAN PUTAR KIPAS ANGIN DAN INTENSITAS LAMPU DENGAN FUZZY LOGIC MAMDANI - Chyquitha Danuputri (Jurnal Algoritma, Logika dan Komputasi, 2020)
Intelligent systems are one of the most important branches of the computer world. Computers are expected to be able to solve various problems in the real world, not just a tool for doing calculations. To make this system, algorithms are needed that are in accordance with the problems faced so that they can solve or produce the decisions needed to solve these problems appropriately. Mamdani fuzzy logic algorithm is one of the algorithms that can be applied in intelligent systems. Fuzzzy mamdani algorithm, is one part of the Fuzzy Inference System which is useful for making the best conclusion or decision in an uncertain problem. This research focuses on the calculation of the fuzzy logic algorithm in providing answers to the uncertainties found in smart home systems used to control the speed of a fan and lights, while the factors that become uncertain in controlling a fan are room temperature and humidity and For lamps, they have a factor of light intensity and time of the region, for these factors, the researchers use the Humanity Guide Hygiene standard reference for humidity and the Regulation of the Minister of Health of the Republic of Indonesia Number 1077 / Menkes / Per / V / 2011 concerning Guidelines for Air Sanitation in Home Spaces. Through this research, it can be seen that using the mamdani fuzzy logic algorithm can provide a result in the form of a decision to determine how fast a fan should rotate based on the temperature and humidity factors in the room as well as the level of light intensity that the lights must emit.